PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA ALFAMART PURI ORCHID CENGKARENG - Fajria Ramadhia; Amirudin (Program Studi Akuntansi Fakultas Ekonomi dan BisnisUniversitas Nusa Nipa, 2025)
The purpose of this study is to determine the influence of Service Quality and Price on Consumer Satisfaction at Alfamart Puri Orchid Cengkareng. The method used is quantitative with a descriptive approach. The sampling data collection technique used the slovin formula and a sample of 100 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that service quality has a significant effect on consumer satisfaction with a determination coefficient value of 67.8% and hypothesis tests are obtained by calculating t > t table or (14.380 > 0.677). Price had a significant effect on consumer satisfaction with a determination coefficient value of 56.4% and the hypothesis test was obtained by calculating t > t table or (11.259 > 0.677). Service Quality and Price simultaneously have a significant effect on consumer satisfaction with the regression equation Y = 4.221 + 0.532X1 + 0.384X2. The value of the determination coefficient was 76.3% while the remaining 23.7% was influenced by other factors. The hypothesis test was obtained with an F value calculated > F table or (155.902 > 3.090).